2022
DOI: 10.3389/fpls.2022.978468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light quality on growth, nutritional characteristics, and antioxidant properties of winter wheat seedlings (Triticum aestivum L.)

Abstract: Wheat seedlings are becoming popular for its high nutritional value. Effects of White (W), White + Red (WR), and White + Blue (WB) light-emitting diodes (LEDs) treatments on growth, nutritional characteristics and antioxidant properties of wheat seedlings were studied in a plant factory. The results showed that height, leaf area, shoot fresh, and shoot dry weight per wheat seedling were the highest under WR at 13 and 22 days after planting. Soluble sugar content in leaves and stems were 22.3 and 65% respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 88 publications
0
2
0
1
Order By: Relevance
“…Em experimento com trigo, Li et al (2022) constataram que o crescimento das plântulas foi significativamente influenciado pelos feixes luminosos, onde a luz vermelha promoveu o crescimento das plântulas, manifestado principalmente como aumento da altura da planta, massa fresca e seca da parte aérea. Por outro lado, Gallardo-Yobal et al ( 2022) averiguaram que a qualidade da luz influenciou a germinação das sementes de Magnolia alejandrae García-Mor.…”
Section: Resultsunclassified
“…Em experimento com trigo, Li et al (2022) constataram que o crescimento das plântulas foi significativamente influenciado pelos feixes luminosos, onde a luz vermelha promoveu o crescimento das plântulas, manifestado principalmente como aumento da altura da planta, massa fresca e seca da parte aérea. Por outro lado, Gallardo-Yobal et al ( 2022) averiguaram que a qualidade da luz influenciou a germinação das sementes de Magnolia alejandrae García-Mor.…”
Section: Resultsunclassified
“…In the present study, we observed that the SOD and POD activities in cassava leaves were significantly elevated by RL treatment but inhibited by BL. In contrast, SOD activity was increased following BL treatment in Rubus hongnoensis [ 40 ], pea [ 41 ] and wheat [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phoebe bournei have encounter many challenges to the environment which imposed by human activities but also natural environment (Li et al 2017), although establishment of most advanced and good seedling with agronomic characteristics but the survival and resistivity of of phoebia bournei remain challenge, under environmental factors like high temperature,salinity and drought (Da 2001). Different studies have shown that the phioebia bournei are more sensitive to biotic stress (Li et al 2022;Wei et al 2023). To ensure the survival and development of the Phoebea bournei population, studying the biochemical and molecular response of Phoebea bournei bZIP under different abiotic stress is very important.…”
Section: Introductionmentioning
confidence: 99%